INSERT model of school mediation for the development of sociocognitive, emotional and moral competences (Journal of Parents and Teachers, 2018)
School mediation is highly beneficial in schools. The number of school mediators, student assistants and cyber mentors in our country continues to grow. The e-AMEDIAR program of Padre Piquer de Madrid, based on the INSERTE model of school mediation and bullying prevention, has since 2005 formed more than 100 mediators and 500 facilitators of intelligent conflict resolution (RIC).
Keywords: school mediation; educational mediation; e-AMEDIAR; conflict resolution; development of competences; coexistence; bullying prevention; bullying